2019
DOI: 10.17305/bjbms.2019.4474
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of PD-L1 expression and CD8+ TIL intensity between NSCLC and synchronous brain metastases

Abstract: Programmed death-ligand 1 (PD-L1) is suggested to be a predictive biomarker in non-small-cell lung carcinoma (NSCLC). However, the differential expression of PD-L1 in primary lung tumor vs. synchronous metastases, especially brain metastasis (BM), remains unclear. This study assessed the concordance of PD-L1 expression on tumor cells and tumor infiltrating lymphocytes (TILs) and CD8+ TIL intensity between primary lung tumors and synchronous BMs from 24 NSCLC patients. PD-L1, CD3, and CD8 positivity was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…The PD-1/PD-L1 signaling pathway has been shown to transmit inhibitory signals to T lymphocytes and promote immune evasion of cancer cells (53). Batur et al reported that the concordance of the PD-L1 expression on cancer cells was high between primary NSCLCs and their synchronous brain metastases (54). According to our data, there was also significant concordance between the PD-L1 expression of cancer cells in primary tumors and lymph node metastases.…”
Section: Discussionsupporting
confidence: 81%
“…The PD-1/PD-L1 signaling pathway has been shown to transmit inhibitory signals to T lymphocytes and promote immune evasion of cancer cells (53). Batur et al reported that the concordance of the PD-L1 expression on cancer cells was high between primary NSCLCs and their synchronous brain metastases (54). According to our data, there was also significant concordance between the PD-L1 expression of cancer cells in primary tumors and lymph node metastases.…”
Section: Discussionsupporting
confidence: 81%
“…[22,27,28,39,40,44,52,53], four studies reported PD-L2[22,29,44,62], twelve studies reported TIL[20,29,30,43,46,[69][70][71][72][73][74][75], five studies reported TMB[23,30,[76][77][78], and six studies reported MSI status…”
mentioning
confidence: 99%
“…However, density of CD8+ TILs was concordant in only 54.16% of the paired primary lung tumors and BMs. 34 In terms of clinical efficacy, a large, multicenter retrospective analysis of NSCLC patients with new and/or growing BM without any previous local therapy reported similar intracranial (27.3%) and extracranial (22.7%) response rates with immune checkpoint inhibitor based treatment. 35 …”
Section: Biomarkers In Bm From Lung Cancermentioning
confidence: 95%